Digestibility of Dry Matter and Organic Matter of Fermented Sago Pulp on Local Sheep Male Weaning - A A Sembiring; T H Wahyuni; N D Hanafi; A H Daulay; Hasnudi (Talenta Publisher, 2018)
This study aims to analyze the digestibility of dry matter and organic matter of fermented sago pulp alternative feed on local sheep male weaning. Research conducted at Karang Rejo village farm, Stabat district, Langkat. This study in Maret 2016-Juny 2017. The design used was completely randomized design (CRD), with four treatments five replications. Each repeat consists of one local sheep male weaning with the average of body weight 8-10 kg. The treatment consisted of P1(consentrat with 50% sago pulp without fermented + forage), P2 (consentrat with 60% sago pulp without fermented + forage), P3 (consentrat with 50% sago pulp fermented + forage), and P4 (consentrat with 60% sago pulp fermented + forage). The variable were studied dry matter consumption, organic matter consumption, dry matter digestibility and organic matter digestibility. Results of analysis of variance show that the utilization of fermented sago pulp waste had highly significantly different effect (P<0,01) on dry matter consumption of treatment P1, P2, P3 and P4 is 486,38; 548,68; 604,69;and 671,11 (gr/head/day), and organic matter consumption is 469,34; 525,22; 582,42 and 644,40 (gr/head/day). And average of dry matter digestibility waste not significantly different effect (P>0,05) on value dry matter digestibility of treatment P1, P2, P3 and P4 is 79,04; 79,23; 78,59 and 78,23 (%), average of organic matter digestibility is 81,66; 81,43; 80,79 and 80,27 (%). Increasing use of fermented pulp sago increases the value of dry matter consumption and organic matter consumption in local sheep feed. Conclusions of fermented sago pulp can not to increase dry matter digestibility and organic matter digestibility, but fermented and non-fermented sago pulp can be given to sheep male weaning up to 60%, because the digestibility value of the two ingredients is above 70%.